2005
DOI: 10.1111/j.1467-6494.2005.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Approach and Avoidance Social Motives and Goals

Abstract: It was predicted that approach social motives and goals would be linked to outcomes characterized by the presence of positive social features, and avoidance social motives and goals would be linked to outcomes characterized by the presence of negative social features and that the link between approach motives and outcomes would be mediated by different processes than the link between avoidance motives and outcomes. These hypotheses were examined in three studies (two of them longitudinal) that measured partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
497
2
13

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(558 citation statements)
references
References 72 publications
(77 reference statements)
36
497
2
13
Order By: Relevance
“…This finding is consistent with previous research indicating that nostalgia regulates avoidance motivation and brings on line approach motivation (Stephan et al, 2104) and with the hierarchical model of approach-avoidance of social motivation (Gable, 2006;Gable & Impett, 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous research indicating that nostalgia regulates avoidance motivation and brings on line approach motivation (Stephan et al, 2104) and with the hierarchical model of approach-avoidance of social motivation (Gable, 2006;Gable & Impett, 2012).…”
Section: Resultssupporting
confidence: 93%
“…Taken together, nostalgia brings on line approach motivation (Stephan et al, 2014) and approach motivation predicts the adoption of social approach goals like meeting new friends and deepening relationships (Gable, 2006;Gable & Impett, 2012;Elliot, Gable, & Mapes, 2006).…”
mentioning
confidence: 99%
“…In an influential paper, Elliot and Thrash (2002) linked domain-general, dispositional approach and avoidance temperaments, conceptualized as the behavioral activation system (BAS) and behavioral inhibition system (BIS; Gray, 1982), to approach and avoidance goals in the achievement domain (a similar result has been found for the affiliation motive; Gable, 2006). Although these authors only argued within the achievement domain, their line of reasoning suggests that a fundamental BIS sensitivity is a temperamental base for all avoidance motives.…”
Section: The Structure Of Motivesmentioning
confidence: 88%
“…prosocial behaviors). Further, prior findings have indicated that the pursuit of prosocial goals and behaviors is negatively associated with loneliness (Gable, 2006). Thus, it appears that for children who are victimized by peers, having a prosocial behavioral tendency that increases social engagement may serve as a protective factor against loneliness.…”
Section: A Theoretical Frameworkmentioning
confidence: 96%